The Role of Telecommunications Services in Regional Economic Growth: Evidence from ECOWAS Zone - WONYRA, Kwami Ossadzifo (International Journal of Economics, Business and Management Studies, 2019)
This study aims to investigate the effects of telecommunication infrastructure on economic growth in ECOWAS countries. The analysis in this article focuses on the effects of telecommunications infrastructure in terms of demand, supply and effects on per capita income. From the point of view of empirical strategy, the triple least square (3SLS) technique is used. This technique provides coefficients for all structural equations and endogeneity bias. The results show that the increase in telecommunications infrastructure raises operators’ revenues and therefore their earnings. Thus, the results show the positive effect of the expansion of both mobile and fixed telephone infrastructure on per capita income. As for implications, it will be necessary to strengthen the role of regulatory authorities both in their ability to ensure competition in the sector and in the promotion of infrastructure to bring countries closer to achieving the objective of universal services.